Entropy Generation Minimization Theoretical Analysis for External Flow Around Horizontal Cylinder at low Reynold Number - Louay Mahdi (Engineering and Technology Journal, 2018)
The minimization of entropy generation is a helpful method to design optimum thermal system, and find an expression for entropy generation at several ranges of Reynolds number for heat transfer and friction flow irreversibility is a good way to achieve this goal. This study deal with several ranges of Reynolds number that cover 0.1< Re< 40000 divided into four groups. A relation between optimum Reynolds number, entropy generation number, irreversibility distribution ratio, and Began number was obtained. In addition, a relation between the optimum Reynolds number and the duty parameter was obtained for all Reynolds number ranges.